2004
DOI: 10.3758/bf03196872
|View full text |Cite
|
Sign up to set email alerts
|

Processing strategies and the generation effect: Implications for making a better reader

Abstract: When presented with items that must be generated versus read at encoding, individuals typically remember better those items that they generated versus those that they only read. We examined whether--given the opportunity to experience such differential memorial consequences of generating versus reading--participants might change how they processed future to-be-read information. In a first set of two experiments, participants were able to profit from such an experience to the extent that a generation advantage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
134
1
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(150 citation statements)
references
References 38 publications
14
134
1
1
Order By: Relevance
“…The important pedagogical implication of the absence of a generation effect in our three replications of the present experiment, as well as in deWinstanley and Bjork's (2004) research, is that it might be easy for a savvy educator to produce a generation effect and thereby greatly enhance his or her students' learning. The read condition in our follow-up experiments, in which a large generation effect was manifested, was such that the learner could passively read (or maybe even not read) the materials.…”
Section: Self-generationsupporting
confidence: 54%
“…The important pedagogical implication of the absence of a generation effect in our three replications of the present experiment, as well as in deWinstanley and Bjork's (2004) research, is that it might be easy for a savvy educator to produce a generation effect and thereby greatly enhance his or her students' learning. The read condition in our follow-up experiments, in which a large generation effect was manifested, was such that the learner could passively read (or maybe even not read) the materials.…”
Section: Self-generationsupporting
confidence: 54%
“…Metcalfe and Kornell (in press), and deWinstanley's group (deWinstanley & Bjork, 2004;deWinstanley, Bjork, & Bjork, 1996) have found that the generation effect is not always in evidence when performance on the generate items is compared to a control condition in which items were presented to the students. The reason for this apparent failure of a well-replicated laboratory finding may not be that the generation effect itself is not robust, however, but rather that it may be too robust.…”
Section: Resultsmentioning
confidence: 99%
“…If, as deWinstanley and Bjork (2004) speculated, the opportunity for participants to experience the generation advantage in their own memory performance leads them to develop more effective encoding strategies, then some of their responses might reflect this awareness. deWinstanley and Bjork (2004) coded any mention by participants of their thinking that they remembered words better when they had "to complete" them or had "to figure" them "out" as indicating an awareness of a recall advantage for generated items; accordingly, just over half of the participants revealed this awareness. Most of these participants then processed the to-be-read items in the second passage more effectively, as indicated by their improved recall of such items.…”
Section: Sensitivity To Generation As An Effective Condition Of Learningmentioning
confidence: 99%
“…These findings raise many interesting questions-some regarding the underlying cause of the effect observed by deWinstanley and Bjork (2004), and some regarding how these findings might best be applied to educational practices. Certainly a critical question concerns the effect's durability.…”
Section: Remaining Questions and Potential Applicationsmentioning
confidence: 99%
See 1 more Smart Citation